Research on the coordination of energy in China's economic growth. - Yuanying Chi (Public Library of Science (PLoS), 2021)
This study uses the improved Cobb-Douglas two-factor production function model to explore the potential relationship between economic growth and energy consumption through the multiple co-integration test on the panel data of China from 1985 to 2018. The results show that there is a positive long-term balance between energy consumption and economic growth: economic growth of 1%, total energy consumption growth of 1.53%, which means that economic growth needs higher energy support in the former short term. At the same time, the error correction term will converge energy consumption to a long-term equilibrium state with an adjustment intensity of 134.59%. From the results of variance decomposition, we can also see that as the number of periods increases, the part of real economic growth explained by energy consumption gradually increases.